Gastric and duodenal polyps in familial polyposis coli. Issue 5 (May 1981) - Ranzi, T; Castagnone, D; Velio, P; Bianchi, P; Polli, E E
Abstract : Endoscopy with multiple biopsies of the upper gastrointestinal tract was repeated yearly over a two to six year period in nine patients with familial polyposis coli from three families. Adenomatous polyps, one to 20 in number and 2-8 mm in size, were detected in the antrum and the first and second duodenal portions in seven patients, while hyperplastic polyps were detected in four patients in the gastric body. In two patients adenomatous tubules were observed in the biopsies of endoscopically normal mucosa from the same area where adenomatous polyps later developed. Lymphoid polyps were detected in the antrum in three cases. Double contrast radiology correlated poorly with endoscopy in the gastric body; it allowed detection of polyps in the third duodenal portion in two more patients. These results confirm that the incidence of adenomas in the upper gastrointestinal tract in familial polyposis coli may be higher than previously suspected.